An Analysis Stylistic of Javanese Women's Language in the movie Tilik the series - Elsa febia kusuma (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
This study aims to analyse the language style of Javanese women in the film Tilik the series as well as understanding the linguistic context in a character in the film. This research focuses on identifying the characteristics of Javanese women who like to gossip and are chatty about phenomena in the surrounding environment. Javanese women in this movie dominate the character Avoidance of strong swear words, Tag questions, Hedges,Intensifiers and Empathic stress. This research uses a descriptive qualitative method whose data is quoted from the dialog script in the film. The research findings show that how Javanese women's language is influenced by socio-culture and represents Javanese women's language style in the movie.